Study of The Comfort of Glamping Tourism Supporting Facilities in The Ciwidey Tourism Area, Bandung Regency, West Java - Nabila, Affra Siti; Alifa, Yumna (Riviera Publishing, 2024)
Camping is one of the activities that interact directly with nature; besides that, camping can build intimacy with the people around us. Camping with comfortable facilities, commonly called Glamour Camping or abbreviated by the term Glamping, is a luxury camping that is a favourite of the world community, including Indonesia. Bandung Regency, especially Ciwidey, has a lot of natural potentials, one of which is Camping Site pine trees, lakes, tea and coffee plantations. Various activities that can be done in the Ciwidey Tourism Area include camping, outbound, water sports, and sightseeing. However, there are not many studies that specifically explore the comfort aspects of tourist support facilities, especially for the Glamping Tourism typology. The purpose of this study is to determine and identify the comfort aspects of Glamping Tourism supporting facilities in the Ciwidey Tourism Area, Bandung Regency, West Java. The method used in this research is a descriptive method with a qualitative approach involving 2 (two) variables, namely the actual condition of tourism and comfort & cleanliness. Data collection techniques were carried out through field observation, documentation studies, and questionnaires. The data collected was then analyzed descriptively and also used SWOT analysis with supporting data from the results of the tourist questionnaire. The results of the analysis of this study concluded that - Tourist responses to glamping tourism facilities in terms of physical conditions show that the available facilities are quite good, but there is still a need for a development strategy for glamping tourism facilities in the wider tourist area by maintaining facilities and maintaining glamping tourism facilities in terms of quality and quantity, collaborating with many parties, following the development of tourism trends.